Implementasi Total Quality Management (TQM) dalam Mewujudkan Sekolah Unggulan di Raudhatul Athfal (RA) As - Sholeh Gumilir Kecamatan Cilacap Utara - Kabupaten Cilacap - Sakiyem Sakiyem (LPPM IAINU Kebumen, 2021)
Abstract Improving the quality of education related to the condition of educational institutions. The quality of educational institutions can be done by applying the concept of Total Quality Management (TQM). In this regard, this study aims to determine Quality Planning, Quality Control, and Quality Improvement in Creating Excellent Schools at RA As Sholeh Gumilir, North Cilacap District, Cilacap Regency. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. This research resulted in the conclusion that: (1) Quality Planning in Creating Excellent Schools at RA As Sholeh Gumilir, North Cilacap District, Cilacap Regency is carried out by determining the quality targets that must be implemented, which can be seen from the vision, mission, and goals that have been predetermined; (2) Quality Control in Creating Excellent Schools at RA As Sholeh Gumilir, North Cilacap District, Cilacap Regency is shown by having a strong commitment and will and continuing to make every effort to improve quality and work based on quality. This is proven by the characteristics and elements of TQM that have been implemented in these madrasas; (3) Quality Improvement in Creating Excellent Schools in RA As Sholeh Gumilir, North Cilacap District, Cilacap Regency is carried out by continuously improving the quality of students, developing learning programs every year, maximizing the role of madrasah organizations, and increasing the human resources of educators and education staff . Keywords: Implementation, Total Quality Management (TQM), Featured Schools